The Analysis of Factors that Affect Students Anxiety in Speaking for Presentation Class (A Study of the Fourth Semester Students at the English Education Study Program of University of Bengkulu in Academic Year 2018/2019) - Nadia Agustin; Mulyadi .; Elfrida . (Universitas Bengkulu, 2019)
This research attemted to find out the factors that affect students speaking anxiety in speaking for presentation class. This research was carried out by employing descriptive quantitative design. The population of this research was the fourth semester students of English Education Study Program of University of Bengkulu in academic year 2018/2019. The samples of this research were taken by using random sampling tehcnique, the total of the sample was 57 students. The data were collected by questionnaire consisted of 29 questions related to the anxiety. The results of this study showed that the students mostly had the mildly anxiety. There were three factors that causing the anxiety of the students in speaking; Fear of Negative Evaluation (Mildly Affected; Mean Score: 3.12), Communication Apprehension (Mildly Affected; Mean Score: 3.09), and Test Anxiety (Mildly Affected; Mean Score: 2.89). In conclusion, there were three factors that students speaking anxiety in speaking for presentation class and the most dominant factors is the Fear of Negative Evaluation